Flow above and within granular media composed of spherical and non-spherical particles – using a 3D numerical model. (1st April 2016) - Bartzke, Gerhard; Kuhlmann, Jannis; Huhn, Katrin
Abstract: The entrainment of single grains and, hence, their erosion characteristics are dependent on fluid forcing, grain size and density, but also shape variations. To quantitatively describe and capture the hydrodynamic conditions around individual grains, researchers commonly use empirical approaches such as laboratory flume tanks. Nonetheless, it is difficult with such physical experiments to measure the flow velocities in the direct vicinity or within the pore spaces of sediments, at a sufficient resolution and in a non-invasive way. As a result, the hydrodynamic conditions in the water column, at the fluid-porous interface and within pore spaces of a granular medium of various grain shapes is not yet fully understood. For that reason, there is a strong need for numerical models, since these are capable of quantifying fluid speeds within a granular medium. A 3D-SPH (Smooth Particle Hydrodynamics) numerical wave tank model was set up to provide quantitative evidence on the flow velocities in the direct vicinity and in the interior of granular beds composed of two shapes as a complementary method to the difficult task of in situ measurement. On the basis of previous successful numerical wave tank models with SPH, the model geometry was chosen in dimensions of X =2.68 [m], Y =0.48 [m], and Z =0.8 [m]. Three suites of experiments were designed with a range of particle shape models: (1) ellipsoids with the long axis oriented in the across-stream direction, (2) ellipsoids with the long axis oriented in the along-stream direction, and (3) spheres. Particle diameters ranged from 0.04 [m] to 0.08 [m]. A wave was introduced by a vertical paddle that accelerated to 0.8 [m/s] perpendicular to the granular bed. Flow measurements showed that the flow velocity values into the beds were highest when the grains were oriented across the stream direction and lowest in case when the grains were oriented parallel to the stream, indicating that the model was capable to simulate simultaneously the flow into and within a granular medium composed of spherical and non-spherical shapes under wave forcing. It is concluded that variations in grain shape orientation within a bed appear to control the amount of flow that can be accumulated by the pores, which was illustrated in a conceptual model. Highlights: 3D numerical wave tank model using Smooth Particle Hydrodynamics (SPH). Simulation of hydrodynamics above and within porous media under wave forcing. Investigation of the influence of grain orientation as well as grain shape.